Interpretive Accommodations for National Park Service Visitors who are d/Deaf or Hard of Hearing. Issue 1 (April 2017) - Hansen, Elsa; Ernst, Julie; Washburn, Julia
Interpretation plays a critical role in fulfilling the mission of the National Park Service (NPS). This study used survey research to describe the interpretive accommodations currently provided to NPS visitors who are d/Deaf or hard of hearing (HoH). Results show that most park units have completed accessibility assessments and provide some form of interpretive accommodations for visitors who are d/Deaf or HoH. However, many park units perceived their unit was not sufficiently meeting the needs of visitors who are d/Deaf or HoH, and felt that their unit should be doing more. Perceived barriers to providing interpretive accommodations included budget and staffing constraints, lack of familiarity with possible services used by visitors who are d/Deaf or HoH, and limited knowledge of legal responsibilities or guidelines pertaining to visitors who are d/Deaf or HoH. Recommendations stemming from this study include the following: staff training; incorporation of the Principles of Universal Design; inclusion of individuals who are d/ Deaf or HoH in planning and evaluation of interpretive services; regular assessments for accessibility; personal and agency-level commitment toward equitable service; use of websites as source of information regarding interpretive accommodations; development of Standard Operating Procedures (SOPs) for accommodative services; creation of a collateral duty for general accessibility; and additional research regarding what services visitors who are d/Deaf or HoH would find most useful to prioritize limited time and budget.